2009
DOI: 10.1021/jm9010669
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Potent Nicotinamide Phosphoribosyltransferase Inhibitor Synthesized via Click Chemistry

Abstract: The inhibition of NAD synthesis or salvage pathways has been proposed as a novel target for antitumoral drugs. Two molecules with this mechanism of action are at present undergoing clinical trials. In searching for similar novel molecules, we exploited copper-catalyzed [3 + 2] cycloaddition between azides and alkynes (click chemistry) to synthesize 185 novel analogues. The most promising compound displays an IC(50) for cytotoxicity in vitro of 3.8 +/- 0.3 nM and an IC(50) for NAD depletion of 3.0 +/- 0.4 nM. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 33 publications
3
69
0
1
Order By: Relevance
“…Likewise, we had previously shown that SNB-19 and SNB-75, two other cell lines, were sensitive to NADdepleting agents (Colombano et al, 2010). These data, together with the immunohistochemical data showing the presence of NAMPT in these tumors, suggests that these agents might have a role in neuroblastoma therapy.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Likewise, we had previously shown that SNB-19 and SNB-75, two other cell lines, were sensitive to NADdepleting agents (Colombano et al, 2010). These data, together with the immunohistochemical data showing the presence of NAMPT in these tumors, suggests that these agents might have a role in neuroblastoma therapy.…”
Section: Discussionsupporting
confidence: 68%
“…Viability of cells was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium assay as described elsewhere (Colombano et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[159] The most promising compound displayed an IC 50 for cytotoxicity in vitro of (3.8 AE 0.3) nm and an IC 50 for nicotinamide adenine dinucleotide (NAD) depletion of (3.0 AE 0.4) nm.…”
Section: Antifungal and Antibacterialsmentioning
confidence: 99%
“…[4] [5] On the other hand, 1,2,3-triazoles present a great stability under acidic, basic, and oxidative conditions. [6] A number 1,2,3-triazole derivatives show good or excellent anticancer activity.…”
mentioning
confidence: 99%